Global health policies that support the use of banked donor human milk: a human rights issue - Arnold Lois DW (BMC, 2006)
Abstract This review examines the role of donor human milk banking in international human rights documents and global health policies. For countries looking to improve child health, promotion, protection and support of donor human milk banks has an important role to play for the most vulnerable of infants and children. This review is based on qualitative triangulation research conducted for a doctoral dissertation. The three methods used in triangulation were 1) writing as a method of inquiry, 2) an integrative research review, and 3) personal experience and knowledge of the topic. Discussion of the international human rights documents and global health policies shows that there is a wealth of documentation to support promotion, protection and support of donor milk banking as an integral part of child health and survival. By utilizing these policy documents, health ministries, professional associations, and donor milk banking associations can find rationales for establishing, increasing or continuing to provide milk banking services in any country, and thereby improve the health of children and future generations of adults.